Dual Cross-Linked Starch–Borax Double Network Hydrogels with Tough and Self-Healing Properties - Xiaoyu Chen; Na Ji; Fang Li; Yang Qin; Yanfei Wang; Liu Xiong; Qingjie Sun (Foods, 2022)
Herein, we have fabricated starch–borax double cross-linked network (DC) hydrogels with tough and self-healing properties using a one-pot method. The addition of borax significantly increased the storage modulus and loss modulus of these starch–borax DC hydrogels. The maximum compression stress (~288 kPa) of starch–borax DC hydrogels containing 5% borax was about ten times greater than that of a pure-starch hydrogel. The texture profile analysis values of the DC hydrogels—including hardness, springiness, cohesiveness, and adhesiveness—increased compared to pure-starch hydrogels. In addition, starch–borax DC hydrogels exhibited excellent self-healing and shape-recovery properties. These DC hydrogels, with a variety of excellent properties, have potential applications in agricultural, biomedical, and industrial fields.